Clinical teaching in primary care: a professional commitment beyond goodwill - Millán Hernandez, Manuel; Albarrán-Pérez, Daniela Francelia (Spanish Journal of Medical Education, 2025)
This letter to the editor comments on the article addressing the barriers perceived by clinical tutors in primary health care settings in Chile. From the perspective of two Family Medicine Specialists, the relevance of the study is acknowledged, and the need to address structural limitations such as lack of time, incentives, and adequate physical space is reinforced. The importance of pedagogical training for professionals involved in clinical teaching is also emphasized. The letter suggests complementing these findings with qualitative research and calls for a renewed recognition of clinical teaching in primary care as a professional commitment beyond goodwill.